¿Leer como espectadores o partícipes críticos? - Fallas Escobar, Christian (2018)
This paper offers a critique on the tendency to give priority to reading comprehension strategies on a superficial level, at the expense of other strategies requiring foreign language learners to read more critically to evaluate the meaning within texts. It also reports on the results of a study conducted with a group of students on the implementation of critical reading tasks, and offers an analysis of the experience, thus providing caveats as to the possible pitfalls of bringing critical literacy into reading courses and English as a Foreign Language programs.